Performance and Transaction Monitoring Dashboard Website Based PT Emporia Digital Raya - Evania Chrestella Albertina; Albertus Dwiyoga Widiantoro; Agus Cahyo Nugroho (SISFORMA, 2024)
Performance and Transaction Monitoring Dashboard Website Based PT. Emporia Digital Raya was to find out performance of business partners, area leader, main dealer and approval of business partners that have been acquired for the company. This dashboard is made to make it easier for companies and product owners to monitor acquisition, transactions through an integrated and non-manual system to minimize errors. Performance and Transaction Monitoring Dashboard was developed using the initial UI design method to describe all the functions that will be available on the web, then developed with reactJS library and JavaScript language, API, and PostgreSQL as database. The testing phase uses technology adoption with a focus on validity, reliability, and AVE test variables after distributing questionnaires to all website users, internal team of PT. Emporia Digital Raya using quantitative methods by classifying each question in the questionnaire. Then the result is that there are several test variables that are not valid in the validity test because they have an item validity value or the validity of the question variable is below 0.4, then the variable must be removed and retested, and after the second test, the results show that the variable has the above item validity value. 0.4 so it is considered valid. In the first validity test, the variable E was declared invalid due to an error in the classification of the questionnaire and did not represent an indicator, so that the variable E was not included in the next test. In the reliability test, only BI and EE variables have high or acceptable Cronbach alpha values, while FC (poor) and PE (unacceptable) or unreliable due to the incorrect classification of questions on the questionnaire causing the variables to be unreliable to be used in further research. In the correlation test, only PE and FC were significantly correlated with BI, while EE was not significantly correlated due to errors in the classification of the questionnaire so that it did not match the variables.